One year of near-continuous fire monitoring on a continental scale: Comparing fire radiative power from polar-orbiting and geostationary observations - Konstantinos Chatzopoulos-Vouzoglanis; Karin J. Reinke; Mariela Soto-Berelov; Simon D. Jones (International Journal of Applied Earth Observations and Geoinformation, 2023)
Geostationary and polar-orbiting remote sensors have different opportunities to observe wildfires. While polar-orbiting sensors have been favoured in wildfire observations, geostationary sensors offer a higher observation frequency. Here, we assess the utility of the Himawari-8 AHI geostationary product and compare it to established polar-orbiting observations from TERRA/AQUA MODIS and SNPP VIIRS for 12 months of fire activity in Australia (2019–2020). Fire Radiative Power (FRP) estimates from AHI (BRIGHT/AHI) are compared to the MODIS (MOD14/MYD14) and VIIRS (VNP14IMG) polar-orbiting products, through varying spatial and temporal aggregations. Results suggest that all products capture similar wildfire dynamics across the continent. For near-simultaneously observed hotspots, the agreement is high between BRIGHT/AHI and the individual polar-orbiting products (r = 0.74–0.77, p < 0.01). Land cover and region-specific comparisons show similar FRP estimate distributions between products, although with scale differences due to the varying spatial resolutions. Derived diurnal FRP cycles on the other hand, highlight the dense temporal information that BRIGHT/AHI offers in contrast to the other products. This is further emphasized with individual event comparisons, where BRIGHT/AHI reports fire activity continuously while the polar-orbiting products only offer fragmented observations when available. In conclusion, AHI observes similar spatiotemporal patterns and FRP estimation distributions to MODIS and VIIRS during different seasons across Australia. While BRIGHT/AHI’s coarser spatial resolution underestimates the FRP estimations captured by its counterparts, its higher observation frequency demonstrates significant advantages. This analysis further raises the confidence in BRIGHT/AHI for continuous wildfire monitoring across Australia while revealing new opportunities that take advantage of its denser observation record.